Effectiveness of Student-Facilitated Problem-Based Learning in Integrated Basic Medical Sciences: A Retrospective Quantitative Analysis of Academic Records - Joshi, Lok Raj; Nembang, Penchha; Hamal, Deependra; Thakur, Chandan Kumar; Anu, Anuraj; Jha, Jay Prakash; Amgain, Kapil (Journal of Institute of Medicine Nepal, 2024)
Introduction Problem-based learning (PBL) is considered as a historic innovation in medical education. However, shortage of experienced faculty tutors for PBL is a major challenge in resource-limited settings. We aimed to assess effectiveness of student-facilitated PBL in content knowledge at a medical college of Nepal. Methods This observational study analyzed the outcome and experience of the PBL modules. This article reports the quantitative analysis which compared pretest and posttest results of the students on multiple-choice questions to assess content knowledge. The maximum possible score was 30 for each test and pass score was set as per modified Angoff method. Results Pretest and posttest results of 53 medical students were analyzed. The results showed that 39 (74%) students passed the pretest and 48 (91%) passed the posttest. This improvement was statistically significant (McNemar's chi-squared=4.27, p=0.04). The median (interquartile range) of the pretest scores was 19(17-21) and that of the posttest scores was 23(21-25) with a significant increase after the PBL module (Wilcoxon signed rank test, p<0.001, effect size=0.67). The posttest scores of the first year students were comparable to the posttest scores of the second year students (Wilcoxon rank sum test, p=0.40). Conclusion The student-facilitated PBL module was effective for improving content knowledge. Future, prospective experimental design with control group may rule out the role of other extraneous variables.